2019
DOI: 10.1080/16089677.2018.1553378
|View full text |Cite
|
Sign up to set email alerts
|

A five-year audit of lower limb amputations below the knee and rehabilitation outcomes: the Durban experience

Abstract: Lower limb amputation (LLA) due to diabetes mellitus (DM) is a growing epidemic worldwide. Objectives: To determine the prevalence of LLAs at Addington Hospital from 2010 to 2014 and to explore the rehabilitation outcomes of amputees. Design and setting: A retrospective chart review of LLAs below the knee was undertaken at Addington Hospital. Subjects: Patients who underwent LLAs were filtered from theatre registers. Methodology: A data collection sheet included demographic profile, diabetic status, level of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Spoden et al established that in Germany alone, the number of lower leg amputation cases was 52,096 in 2005 and 55,595 in 2015, confirming that a significant population suffers from lower leg amputations and it is on the increase [ 1 ]. A study by Manickum et al suggests that 53.1% of lower leg amputations are caused by Diabetes Mellitus alone [ 2 ]. In India, Pooja et al performed a study of 155 amputees and observed trauma to be the primary cause of amputation (70%) followed by vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Spoden et al established that in Germany alone, the number of lower leg amputation cases was 52,096 in 2005 and 55,595 in 2015, confirming that a significant population suffers from lower leg amputations and it is on the increase [ 1 ]. A study by Manickum et al suggests that 53.1% of lower leg amputations are caused by Diabetes Mellitus alone [ 2 ]. In India, Pooja et al performed a study of 155 amputees and observed trauma to be the primary cause of amputation (70%) followed by vascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 2 million people in the United States have undergone limb amputation, resulting in approximately 185,000 amputations performed each year [2]. Roughly 60 -70% (nearly 1.2 million people) of these amputations were performed on the lower-limb, with the majority being below-knee, transtibial amputation [3]. The leading causes of lower-limb amputations are due to diabetes mellitus and other diseases associated with it, such as peripheral vascular disease, cardiovascular disease, and obesity [3]- [5].…”
Section: Introduction Motivationmentioning
confidence: 99%
“…Roughly 60 -70% (nearly 1.2 million people) of these amputations were performed on the lower-limb, with the majority being below-knee, transtibial amputation [3]. The leading causes of lower-limb amputations are due to diabetes mellitus and other diseases associated with it, such as peripheral vascular disease, cardiovascular disease, and obesity [3]- [5]. It is estimated that the number of amputations caused by these vascular diseases could double by the year 2050 [2].…”
Section: Introduction Motivationmentioning
confidence: 99%
See 2 more Smart Citations